1977
DOI: 10.1021/jm00216a014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antileukemic activity of 5-substituted 2,3-dihydro-6,7-bis(hydroxymethyl)-1H-pyrrolizine diesters

Abstract: Treatment of N-acylproline derivatives, 2, with acetic anhydride--dimethyl acetylenedicarboxylate (DMAD) gave 5-substituted derivatives of dimethyl 2,3-dihydro-1H-pyrrolizine-6,7-dicarboxylate (5). The reaction proceeds via a 1,3-dipolar addition of DMAD with the mesoionic oxazalone intermediate 3, generated in situ, with concomitant elimination of carbon dioxide. Reduction of 5 gave the diols 6 which upon subsequent acylation gave 1. The bis(N-methylcarbamate) 1d and the diacetate li show a modest level of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…Our initial attempts, analogous to the reported methods adopted for the pyrrole diesters [4, 5, 25], to reduce the tetra ester with lithium aluminum hydride (LAH) in ether or tetrahydrofuran resulted in a low yield of the desired tetra alcohol. The reaction mixture contained a variety of products, presumably owing to incomplete reduction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial attempts, analogous to the reported methods adopted for the pyrrole diesters [4, 5, 25], to reduce the tetra ester with lithium aluminum hydride (LAH) in ether or tetrahydrofuran resulted in a low yield of the desired tetra alcohol. The reaction mixture contained a variety of products, presumably owing to incomplete reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies by Anderson et al . [4–7] have shown that functionalized pyrrole and pyrrolizine derivatives [ e.g. , 1,2,5‐trisubstituted 3,4‐bis(hydroxymethyl pyrrole‐ N ‐methyl carbamate)] 4 and 5 possess potent antitumor activity in vivo analogous to that of the anticancer mitomycins and pyrrolizidine alkaloids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The indolizine core is a privileged heterocyclic ring system found in a large number of bioactive natural alkaloids and clinically useful pharmaceuticals 2. The 5,6,7,8‐tetra‐ and 5,6‐dihydroindolizine frameworks (Figure 1) have recently drawn tremendous interest from both synthetic and medicinal chemists because of their properties as anti‐tumor,3a,g anti‐leukemia,3b anti‐cholinergic agents,2a and other important biological activities 3. In addition, 5,6,7,8‐tetra‐ and 5,6‐dihydroindolizine alkaloids are common secondary metabolites in plants, invertebrates, fungi, and bacteria 4.…”
Section: Methodsmentioning
confidence: 99%
“…For general background to pyrrolizine derivatives, see: Barsoum & Nawar (2003); Abbas et al (2010); Anderson & Corey (1977); Makoni & Sugden (1980); Laufer et al (1997). For a related structure, see: Nirmala et al (2009).…”
Section: Related Literaturementioning
confidence: 99%